(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article we have developed research directions in modern philosophy and image problems of meaning in life, which needs to be addressed in the future: to be reviewed the role of religion and its services in a modern society; should address new issues relating to human problems in the philosophy of religion and related to new scientific discoveries and positions, such as, modern quantum physics, quantum psychology, the theory of synergy, a holographic model of the world, etc. Key words: Religion, philosophy, human, spirituality, moral qualities